Modelling the optical bleaching of the thermoluminescence of K 2YF 5:Pr 3+ - Marcazzo, Salvador Julian (2012)
Optical bleaching of the thermoluminescence (TL) curve of K 2YF 5:Pr 3+ has been observed after optically stimulated luminescence (OSL) readout of pre-irradiated crystals. The traps being responsible for the TL signal are not emptied completely by the optical stimulation. Furthermore, if the illumination time is increased a constant intensity level of the residual TL glow curve is eventually achieved. On the other hand, if the low temperature peak of the glow curve is thermally cleaned, no subsequent OSL is measured. This behavior has been successfully explained by assuming that part of the electrons in the trap being responsible for the low temperature glow peak of K 2YF 5:Pr 3+ recombine with holes via localized transitions during optical stimulation. During TL all trapped electrons recombine via delocalized transitions. Simulations have been carried out in order to demonstrate the feasibility of the model.